2022
DOI: 10.1155/2022/2110636
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles from Rhododendron arboreum for Metal Sensing, Antibacterial Assessment, and Photocatalytic Degradation

Abstract: The nanomaterial industry has focused on green synthetic methods to avoid unpleasant compounds produced during manufacturing, offering eco-friendly, sustainable, and nature-derived alternative methods. In this study, silver nanoparticles (Ag NPs) have been synthesized from an aqueous extract of the leaves of Rhododendron arboreum, where the pH of the reaction mixture is found to be crucial. The reaction progress monitored using the UV-Vis spectrophotometer displayed a strong absorption band at 425 nm at pH 9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…The detected band at 1110.92 cm -1 is due to the C-N stretch of an aliphatic amine group in the protein [ 44 ]. Simultaneously, many spectral bands, 1110.92, 1226.64, 1110.93, 1072.35, 1319.22, 1211.21, 1072.21 cm-1, resulting from C-H stretch owing to alcohols, carboxylic acids, esters, and ethers, as they lie between 1320 and 1000 cm-1, were detected.…”
Section: Resultsmentioning
confidence: 99%
“…The detected band at 1110.92 cm -1 is due to the C-N stretch of an aliphatic amine group in the protein [ 44 ]. Simultaneously, many spectral bands, 1110.92, 1226.64, 1110.93, 1072.35, 1319.22, 1211.21, 1072.21 cm-1, resulting from C-H stretch owing to alcohols, carboxylic acids, esters, and ethers, as they lie between 1320 and 1000 cm-1, were detected.…”
Section: Resultsmentioning
confidence: 99%
“…The detected band at 1110.92 cm -1 is due to the C-N stretch of an aliphatic amine group in the protein [41]. Simultaneously, many spectral bands, 1110.92, 1226.64, 1110.93, 1072.35, 1319.22, 1211.21, 1072.21 cm-1, resulting from C-H stretch owing to alcohols, carboxylic acids, esters, and ethers, as they lie between 1320 and 1000 cm-1, were detected.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Phuyal et al [41], Khodadadi et al [58], and Kaur et al [59] demonstrated more antibacterial activity against Gram-positive bacteria ( S. aureus ) than against Gram-negative bacteria ( E.coli and S. choleraesuius ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations